Fenologia, xenia e irrigação na produção de frutos de nogueira-pecã - Marco , Rudinei de (2020)
One of the fruit species that currently grows the most in economic importance in Brazil is pecan, mainly due to the increased consumption of the fruit and the appreciation of the market. However, with this growth, many problems, doubts and difficulties of communication between those involved with the culture arise, requiring studies that address and establish technical and standardized information, in order to improve the understanding and management of culture through monitoring phenological, pollination and irrigation. Therefore, the objective of the study was to propose and monitor a phenological scale, to evaluate the influence of pollination and irrigation on the dimensions and yields of pecan fruits. To meet the objectives, the work was organized into three chapters. The first is a proposal and application of the BBCH phenological scale adjusted for pecan. In the second chapter, the effect of pollen from different cultivars on the yield and fruit dimensions of ‘Kiowa’ and ‘Barton’ was evaluated. In the third chapter, the use of irrigation on fruit growth and yield was evaluated. From the results obtained it was possible to conclude that the proposed phenological scale is easy to apply and will facilitate scientific and technical communication between professionals in the field and producers. Pollen from different cultivars showed potential positive and negative “xenia effect” on fruit characteristics, while self-pollination reduces the dimensions and yield of fruits and almonds. During the development of pecan fruits, the occurrence of periods of water deficit affects the size and filling of the nuts, and the use of irrigation provides greater dimensions and mass of the fruits.